Limiting the age for candidates of public officials viewed by human rights and moral perspective - Lutfiadi, Lutfiadi; Camelia, Noer Dini; Wardani, Win Yuli; Heryanti, Febrina; Wahyono, Sapto (IHSA Institute, 2024)
Elections are a key requirement of a democratic state. Democracies uphold human rights. There are human rights that can be restricted and Elections are a key requirement of a democratic state. Democracies uphold human rights. There are human rights that can be restricted and those that cannot. The right to be elected and to vote in public office is a human right that can be restricted by the state, but the restriction must be based on reasons that are in line with morality. This research aims to understand whether restrictions on the right to be elected and to vote based on age are in line with the law and morals or vice versa. This research is normative legal research that focuses on the problem of legal norms at the level of positive law, legal theories, and principles. The approaches used are legislation, literature review, conceptual approaches. The result is that all forms of restrictions on the community to participate in state life are restrictions on human rights. Restrictions on human rights are a violation of moral values. The conclusion is that a democratic state should not limit a person's right to vote and elect. The state should leave it entirely up to the people, whether they want to vote for that person or not. The Constitutional Court should not create new norms, the Constitutional Court should only have the authority to declare a certain legal norm contrary to the 1945 Constitution or not